2006
DOI: 10.1080/00131880600992363
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to studying among Greek university students: the impact of gender, age, academic discipline and handedness

Abstract: There is considerable interest in differences in students' approaches to learning, particularly in the difference between 'deep' approaches (characterized by contextualization, critical review and recognition of the value of the content) and 'surface' approaches (characterized by rote learning for functional purposes). The Revised approaches to studying inventory (RASI) attempts to measure approaches but it is suggested that it cannot be applied universally. PurposeThe purpose of the study was to assess the fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 26 publications
0
21
0
5
Order By: Relevance
“…Por otra parte, existen resultados contradictorios en relación a la edad y los enfoques de aprendizaje (26,27) . En nuestro estudio no se hallaron diferencias significativas de los enfoques de aprendizaje en relación al sexo y edad.…”
Section: Discussionunclassified
“…Por otra parte, existen resultados contradictorios en relación a la edad y los enfoques de aprendizaje (26,27) . En nuestro estudio no se hallaron diferencias significativas de los enfoques de aprendizaje en relación al sexo y edad.…”
Section: Discussionunclassified
“…Variations in approaches to learning have been confirmed both on an aggregated level, for example as a matter of discipline being studied (Andreou et al 2006;Baeten et al 2010;Parpala et al 2010), and on individual level, as within students' variation (Nijhuis et al 2008;Vermetten et al 1999). The composition of students' approaches to learning is proposed to develop from a complex process that includes both personal factors, such as gender, age, personality, mental ability and previous studying experiences, and contextual factors, such as feedback procedures, assessment methods and the levelling of student-centred versus teachercentred learning contexts (for an overview, see Baeten et al 2010).…”
Section: Variation In Approaches To Learningmentioning
confidence: 94%
“…Examining the literature on learning approaches, a number of studies conducted in different countries abroad have been found (Andreou, Vlachos, & Andreou, 2006;Bernardo, 2003;Cano, 2005;Cuthbert, 2005;Elias, 2005;Gijbels & Dochy, 2006;Kember & Harper, 1987;Ramsden & Entwistle, 1981;Reid, Duvall & Evans, 2005;Richardson, 1993). In Turkey, although less than the study of the learning approaches abroad, it is seen that there is an increase in recent years (Alemdağ, 2015;Altun, 2013;Çolak & Fer, 2007;Çuhadar, Gündüz, & Tanyeri, 2013;Ekinci, 2009;Doğruluk, 2015;Ekinci, 2015;Ekinci & Ekinci, 2011;Gürlen, Turan, & Senemoğlu, 2013;Kızılgüneş, Tekkaya, & Sungur, 2010;Ozan, Köse, & Gündoğdu, 2012;Ozan & Çiftçi;Senemoğlu, 2011;Sezgin-Selçuk, Çalışkan, & Erol, 2007;Yılmaz & Orhan, 2010).…”
Section: Purposementioning
confidence: 99%